Topology optimization for stability problems of submerged structures using the TOBS method. (15th January 2022) - Mendes, E.; Sivapuram, R.; Rodriguez, R.; Sampaio, M.; Picelli, R.
Highlights: Structural topology optimization involving pressure loads and buckling constraints are considered using a binary approach. The Topology Optimization of Binary Structures (TOBS) method deals with separate domains and creates clear boundary interfaces - a significant advantage for multiphysics TO problems. Two numerical examples are solved: the first one introduces the arch-like problem, discussing design-dependent and design-independent approaches. The piston-head model completes the proposed formulation by analysing the support conditions influence over the stability performance. To the best of the authors' knowledge, this is the first work that considers buckling constraints for TO of fluid pressure loaded structures. Abstract: Structural optimization is increasingly used across academia and industry because of the great design freedom it offers and due to the increasing availability of computational power. In this context, binary methods - which generate clear (0/1) designs - are an effective approach to solve optimization problems, especially multiphysics, wherein precise definition of the structural boundary is essential. This work adopts the Topology Optimization of Binary Structures (TOBS) method to solve structural optimization problems that consider buckling constraints and design-dependent loads, such as fluid pressure loading, a characteristic of submerged structures. Buckling constrained TO problems applied to design-dependent loads are not yet explored in the literature. Few optimization problems are investigated to demonstrate the effect of the buckling constraint on the optimized solutions as compared to that of the classical compliance minimization problem. The common issues associated with the eigenproblem characteristic of the buckling phenomenon are discussed. The method successfully considers design-dependent loads coupled with stability constraints, obtaining final solutions with significant improvement in buckling resistance and minimal stiffness loss when compared to the compliance design. It is concluded that the TOBS method presented promising results and potential application in stability problems of design-dependent loaded structures, such as those present in the offshore industry.